HYMES’ S.P.E.A.K.I.N.G ANALYSIS ON THE EXPRESSIONS USED IN KABASARAN DANCE - Taramen, Isabela (Journal of English Language and Literature Teaching, 2023)
This study was conducted for the following purposes, firstly, identifying the elements of S.P.E.A.K.I.N.G analysis that is found in Kabasaran Dance, secondly, identifying verbal and non-verbal expressions used in Kabasaran Dance and the last is explaining the meaning of those expressions. And it was delimited to Kabasaran dance which used Tombulu language. In conducting this research, descriptive method was used, since the matter of fact that the data are collected in the form of words. This research is classified as a qualitative research, since the data were collected in the form of words, sentences, and expressions, not numbers. The subject of this research is Kabasaran Dance. Specifically, about the expressions that is used by dancers of Kabasaran Dance. The informant was taken from Wailan Village, and the status of the informat is leader of Sanggar Seni Mahsambureyrey Organization. Based on the research conducted in the expressions used in Kabasaran Dance, the data could be concluded that the expressions used in Kabasaran Dance consists of twenty four words, which is each word has a different meaning and it is mostly refers to the commands given by leader of Kabasaran dance. Through this data presented above, it can be improve the reader’s knowledge about Kabasaran Dance. It was suggested that language learners especially the students, should understand the object and the data source to analyze communication utterance using S.P.E.A.K.I.N.G analysis by Dell Hymes